Performance analysis of power generation by wood and woody biomass gasification in a downdraft gasifier - Sahar Safarian; Runar Unnthorsson; Christiaan Richter (Institute of Advanced Engineering and Science, 2021)
An equilibrium simulation model was developed by applying Aspen Plus to evaluate the performance of 28 wood and woody biomass (W&WB) gasification in a downdraft gasifier integrated with power production unit. The developed simulation model does not focus the gasification process as a closed box, it considers important processes in gasification like drying, pyrolysis, combustion, gasification and integrated with power production plant (combustion chamber plus gas turbine). The results for the 28 W&WB alternatives show that the net power produced from 1-ton feedstock entering to the gasification system is between the interval [0-400 kW/ton] and among them, gasification system derived from Tamarack bark biomass significantly outranks all other systems by producing 363 kW/ton, owing to the favorable results obtained in the performance analysis. Moreover, effect of various operating parameters such as gasification temperature and air to fuel ratio (AFR) on the system performance was carried out. Finally, the developed model is applied as an effective tool to assess the impact of so many biomasses and operating parameters on output power.